The triplet state of the ladder-type methyl-poly(p-phenylene) as seen by pulse radiolysis-energy transfer - Monkman, A. P. (2000)
The lowest triplet state of a ladder poly(p-phenylene) (MeLPPP) has been produced by sensitised energy transfer following pulse radiolysis of benzene solution, and absorbs at 1.34 eV with a lifetime [greater-or-equal, slanted]170 [mu]s. An S0-T1 energy separation of 2.15 ± 0.07 eV was determined, in excellent agreement with recent phosphorescence measurements, confirming the validity of the technique for the determination of the triplet energies of conjugated polymers. At high triplet populations intrachain triplet-triplet annihilation (TTA), leading to delayed fluorescence (DF) occurs. The DF spectrum is in good agreement with the prompt fluorescence and the DF kinetics support a TTA mechanism.